Active Surveillance Cultures and Decolonization to Reduce Staphylococcus aureus Infections in the Neonatal Intensive Care Unit. (4th January 2016) - Popoola, Victor O.; Colantuoni, Elizabeth; Suwantarat, Nuntra; Pierce, Rebecca; Carroll, Karen C.; Aucott, Susan W.; Milstone, Aaron M.
Abstract : BACKGROUND: Staphylococcus aureus is a common cause of healthcare-associated infections in neonates. OBJECTIVE: To examine the impact of methicillin-susceptible S. aureus (MSSA) decolonization on the incidence of MSSA infection and to measure the prevalence of mupirocin resistance. METHODS: We retrospectively identified neonates admitted to a tertiary care neonatal intensive care unit (NICU) from April 1, 2011, through September 30, 2014. We compared rates of MSSA-positive cultures and infections before and after implementation of an active surveillance culture and decolonization intervention for MSSA-colonized neonates. We used 2 measurements to identify the primary outcome, NICU-attributable MSSA: (1) any culture sent during routine clinical care that grew MSSA and (2) any culture that grew MSSA and met criteria of the National Healthcare Safety Network's healthcare-associated infection surveillance definitions. S. aureus isolates were tested for mupirocin susceptibility. We estimated incidence rate ratios using interrupted time-series models. RESULTS: Before and after the intervention, 1, 523 neonates (29, 220 patient-days) and 1, 195 neonates (22, 045 patient-days) were admitted to the NICU, respectively. There was an immediate reduction in the mean quarterly incidence rate of NICU-attributable MSSA-positive clinical cultures of 64% (incidence rate ratio, 0.36 [95% CI, 0.19–0.70]) after implementation of the intervention, and MSSA-positive culture rates continued to decrease by 21% per quarter (incidence rate ratio, 0.79 [95% CI, 0.74–0.84]). MSSA infections also decreased by 73% immediately following the intervention implementation (incidence rate ratio, 0.27 [95% CI, 0.10–0.79]). No mupirocin resistance was detected. CONCLUSION: Active surveillance cultures and decolonization may be effective in decreasing S. aureus infections in NICUs. Infect. Control Hosp. Epidemiol. 2016;37(4):381–387